Combination of Anti‐Biofouling and Ion‐Interaction by Click Chemistry for Endotoxin Selective Removal from Protein Solution. Issue 6 (26th November 2012) - Guo, Jinshan; Meng, Fanbo; Jing, Xiabin; Huang, Yubin
<x xml:space="preserve">Abstract</x> A successful combination of anti‐biofouling and ion‐interaction for endotoxin (ET) selective removal from protein solutions is realized via the immobilization of two ordinary polymers, PEG and PLL, which have protein resistance and endotoxin adsorption properties, respectively, together onto azide‐functional polystyrene (PS‐N3) microspheres (MSs) using a surface click reaction. Toxic copper ions residu is successfully minimized by the addition of 2, 2′‐bipyridine (BiPy). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>